2008
DOI: 10.1007/s11427-008-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plant biomass and species composition of alpine Kobresia meadows along altitudinal gradient on the Qinghai-Tibetan Plateau

Abstract: Alpine Kobresia meadows are major vegetation types on the Qinghai-Tibetan Plateau. There is growing concern over their relationships among biodiversity, productivity and environments. Despite the importance of species composition, species richness, the type of different growth forms, and plant biomass structure for Kobresia meadow ecosystems, few studies have been focused on the relationship between biomass and environmental gradient in the Kobresia meadow plant communities, particularly in relation to soil mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 33 publications
2
32
1
Order By: Relevance
“…These results are consistent with the alpine meadow ecosystem in the Tibetan Plateau, where the biomass of the companion species such as legumes, sedges, and forbs was higher than the biomass of the dominant species in the Kobresia pygnaeca meadow, Kobresia humilis meadow, and Kobresia tibetica swamp meadow . The biomass of the alpine steppe in the current study is lower than the biomass of alpine meadow in the Tibetan Plateau reported by Kato et al (2004), Zhao et al (2005), Wang et al (2008), andZhang et al (2009). This is because the habitat of the alpine steppe is harsher, and plant growth is limited by the low temperature and precipitation, as well as the barren soils when compared with the alpine meadow.…”
Section: Discussioncontrasting
confidence: 80%
“…These results are consistent with the alpine meadow ecosystem in the Tibetan Plateau, where the biomass of the companion species such as legumes, sedges, and forbs was higher than the biomass of the dominant species in the Kobresia pygnaeca meadow, Kobresia humilis meadow, and Kobresia tibetica swamp meadow . The biomass of the alpine steppe in the current study is lower than the biomass of alpine meadow in the Tibetan Plateau reported by Kato et al (2004), Zhao et al (2005), Wang et al (2008), andZhang et al (2009). This is because the habitat of the alpine steppe is harsher, and plant growth is limited by the low temperature and precipitation, as well as the barren soils when compared with the alpine meadow.…”
Section: Discussioncontrasting
confidence: 80%
“…Previous studies have shown that above-ground biomass may decrease (Pérez and Frangi 2000;Wang et al 2007Wang et al , 2008, or present a hump-shaped pattern in relation to altitude (Raich et al 1997). For the Hongchiba Fig.…”
Section: Discussionmentioning
confidence: 85%
“…There are many studies relating to biomass structure and species richness so there is considerable information about how these are adapted to altitudinal gradients (Fleishman et al 1998;Pérez and Frangi 2000;Lomolino 2001;Rahbek 1995Rahbek , 2005Wang et al 2007Wang et al , 2008. Nevertheless, patterns of species richness and biomass along altitudinal gradients vary geographically.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations